Radiochemotherapy for invasive bladder cancer : An update - Tselis, N.; Prott, F. J.; Ott, O.; Weiss, C.; Roedel, C. (Urologe, 2018)
BACKGROUND: The standard treatment for muscle-invasive bladder cancer is radical cystectomy with pelvic lymphadenectomy. Primary organ-preservation by means of multimodal therapy, however, can be a viable alternative to radical surgery. OBJECTIVES: The concept and results of multimodal therapy, consisting of initial transurethral resection of the bladder tumor (TUR-B), followed by simultaneous radiochemotherapy (RCT), are presented. MATERIALS AND METHODS: Evaluation of retrospective cohorts and prospective therapy optimization studies on organ-preservation treatment regimens. Comparative meta-analyses comparing cystectomy with multimodal treatment are presented. RESULTS: Complete TUR-B, including bladder mapping and tumor biopsy, should precede simultaneous RCT. Radiosensitization should be cisplatin-based or consist of a combination of 5‑fluorouracil and mitomycin C. Complete response rates after TUR-B plus RCT are generated in 60-90% of patients along with 5‑year survival rates of 40-75% and preservation of the bladder in approximately 80% of surviving patients. CONCLUSIONS: Multimodal therapy by means of TUR-B followed by simultaneous RCT is a viable alternative to radical cystectomy for patients with muscle-invasive urinary bladder carcinoma. Patients with early tumors (cT2/3N0) are particularly suitable in whom initial TUR-B leads to complete tumor resection (R0).
EVALuna2:36530